Usability (US), User Experience (UX) and Methodological Procedures in User × Product Interaction Evaluations - Paschoarelli, Luis C. [UNESP]; Moreira da Silva, Fernando (Springer Nature, 2025)
The User × Product Interaction (UxPI) has aroused the interest of the production sector and academia in new studies and applications, mainly based in the field of Usability (US) and User Experience (UX). Discussions about the scope and skills of these concepts have expanded and can provide strong support for assessments of the UxPI, mainly in the field of product design. This study aims to analyze concepts and scopes of US and UX and their developments, and as a consequence, present some methodological parameters for evaluations on UxPI. The used methodology was Literature Review, crossing and bridging information in a trans and interdisciplinary way. The results present six methodological parameters: 1. State of the art and research question, 2. Characterization and variables of evaluation, 3. Ethical Aspects, 4. Sampling, 5. Definition of the evaluation instruments and procedures, and 6. Parameters for analysis and presentation of the results. These parameters can help professionals and researchers who are interested in UxPI assessments.
Keywords: Product Design; Usability; User-Experience